Thermal maturity and chemical structure evolution of lump long-flame coal during superheated water vapor–based in situ pyrolysis. (15th January 2023) - Zhang, Chao; Zhao, Yangsheng; Feng, Zijun; Meng, Qiaorong; Wang, Lei; Lu, Yang
Abstract: Oil and gas products can be successfully obtained from low-rank coal using superheated water vapor in situ pyrolysis technology, and investigating the pyrolysis properties of coal during this process is crucial. Herein, the in situ pyrolysis of lump long flame coal with superheated water vapor using a proprietary superheated water vapor pyrolysis system was simulated. The vitrinite reflectance (Ro ) and functional groups of coal samples were analyzed using a microscope photometry and Fourier transform infrared spectroscopy. Moreover, the relationship between the chemical structural parameters and vitrinite reflectance during different thermal maturation processes was examined. The results indicate that the vitrinite reflectance increased from 1.01% for raw coal to 2.2% at 550 °C as the pyrolysis temperature increased. The ranges of the critical temperature for the removal of aliphatic structures, C–O, CO, –OH, and aromatic structures from the coal were 271°C-506 °C, 333°C-550 °C, 220°C-550 °C, RT–333 °C, and 333°C-550 °C, respectively. As Ro increased, the aromaticity and condensation both increased linearly and then decreased; the CH2 /CH3 ratio first decreased and then increased; the C-factor exhibited negative exponential reduction. Artificial thermal maturation was more effective than natural thermal maturation in promoting the evolution of the aliphatic structure but less effective in promoting the condensation of aromatic rings. Both types of thermal maturation have the same effect on the evolution of aromaticity and C-factor. Highlights: The effect of superheated water vapor pyrolysis of coal was evaluated. The thermal maturity evolution of coal was characterized by vitrinite reflectance. Chemical structure changes of coal were characterized by FTIR. The relationship between chemical structure parameters and the Ro was quantified.